WAYS TO DEVELOP TAX SYSTEMS IN AGRICULTURAL FORMS OF ECONOMIC MANAGEMENT - Igor Yu. Pelevin (Статистика и экономика, 2016)
Following article devoted to consideration of possible ways to develop tax system in agricultural forms of economic management. Principles of tax reforming for agricultural sector are presented, in addition initial analysis has been done for single agricultural and land tax. The article represents verification of essential support of generality principles for taxation of agrarian firms. Methodology of calculation of tax basis for single agricultural tax has been offered.